5x-3y+11w-2y-4w+7x=

Simple and best practice solution for 5x-3y+11w-2y-4w+7x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3y+11w-2y-4w+7x= equation:


Simplifying
5x + -3y + 11w + -2y + -4w + 7x = 0

Reorder the terms:
11w + -4w + 5x + 7x + -3y + -2y = 0

Combine like terms: 11w + -4w = 7w
7w + 5x + 7x + -3y + -2y = 0

Combine like terms: 5x + 7x = 12x
7w + 12x + -3y + -2y = 0

Combine like terms: -3y + -2y = -5y
7w + 12x + -5y = 0

Solving
7w + 12x + -5y = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-12x' to each side of the equation.
7w + 12x + -12x + -5y = 0 + -12x

Combine like terms: 12x + -12x = 0
7w + 0 + -5y = 0 + -12x
7w + -5y = 0 + -12x
Remove the zero:
7w + -5y = -12x

Add '5y' to each side of the equation.
7w + -5y + 5y = -12x + 5y

Combine like terms: -5y + 5y = 0
7w + 0 = -12x + 5y
7w = -12x + 5y

Divide each side by '7'.
w = -1.714285714x + 0.7142857143y

Simplifying
w = -1.714285714x + 0.7142857143y

See similar equations:

| s+24+5s=9s-37 | | -n-5n=-6 | | 2c+42+37=7c+2 | | 4w+6y+9x+3x-13y+4w= | | v+36+v+50=7v+26 | | 23y^3-36= | | y=4+8x | | w^2=9w^2 | | 3v-30+v+7=3v | | 7w+12x+5y= | | 5a-3=-a+9 | | w+25+47=3w+42 | | 3y+9=3y-6 | | 9+2(5(12)+3)=135 | | 3t+27+11t=23t | | 2x+10+x+5=180 | | 4w+6x+11y+3w+6x-6y= | | 0.25(x+60)-0.03(x-20)=24.4 | | 7-9n=16 | | 4v-32+31=v+49 | | 1/3(3x-17) | | 27*5=n | | 3m+5.4=25.5 | | 9x+18y=-18 | | 3a+5a=5a+45 | | -20/3-10k/3=2k/3-1/3(6k-4) | | 48+17y=24y+27 | | 12x^4-28x^2-24=0 | | 4(2y+2)+10=6(5y+4)-19 | | 10=4c+8 | | 3z-26+2z=z+50 | | (2y-20)+(2y-20)+y=360 |

Equations solver categories